DETERMINING PREDICTORS OF PSYCHOLOGICAL WELLBEING AMONG NURSES IN NHI PILOT CLINICS IN DR KENNETH KAUNDA DISTRICT - Dianne Ackerman; Ruwayda Petrus; Inge Petersen (Social Sciences and Education Research Review)
This paper determines the predictors of psychological well-being among nurses in NHI pilot clinics. Re-engineering of Primary Health Care and the introduction of the National Health Insurance (NHI) in South Africa increased nurses' workload. The study uses a quantitative, cross-sectional design with a sample of 36 nurses. The study used the Psychological Capital questionnaire, Maslach Burnout Inventory, General Health Questionnaire, and Job Content Questionnaire. Results indicate that self-efficacy is the only positive predictor of psychological well-being.